Strategic analysis of the internal environment and its impact on achieving sustainable competitive advantage (Entrepreneurship Journal for Finance and Business, 2023)
This study deals with the strategic analysis of the internal environment and highlighting the strengths that are invested to achieve the goals of the institution and reduce the weaknesses faced by the institution and represent an existing danger to reach the goals of the institution, and the role of those internal dimensions in achieving competitive advantage and maintaining and sustaining it, Knowing the availability of strengths in banking institutions and monitoring and reducing weaknesses that they are exposed to, especially since institutions live in a rapidly changing environment with renewed desires in the tastes of customers, which necessitates achieving a sustainable competitive advantage appropriate to its capabilities and capabilities, which enables the institution to excel in its field of specialization by providing various Unique to its customers and always better than its competitors, This research was applied through the use of data for a number of commercial banks operating in the Middle Euphrates region on a sample of managers working in them with a total number of (100) respondents for the period from 1/8/2022 to 29/9/2022, and a number of statistical analyzes and tests were used. Using the statistical programs (AMOS), (Excel, (Spss), a special measuring tool has been designed to collect the necessary data that serves the research topics.The research has reached a set of conclusions, the most important of which are: Banking institutions are affected by the internal factors of strengths and reduce the weaknesses that institutions are exposed to in order to face competition and competitors, The research concluded with a set of recommendations, the most important of which were: The necessity of analyzing the internal environment of the institutions to find out the appropriate strengths and exploiting them correctly and to reduce the weaknesses that they are exposed to and reduce them or confront them to reach the success of the institution and face market competition.